2019
DOI: 10.1158/2159-8290.cd-18-1522
|View full text |Cite|
|
Sign up to set email alerts
|

Oral Mucosal Organoids as a Potential Platform for Personalized Cancer Therapy

Abstract: Previous studies have described that tumor organoids can capture the diversity of defined human carcinoma types. Here, we describe conditions for long-term culture of human mucosal organoids. Using this protocol, a panel of 31 head and neck squamous cell carcinoma (HNSCC)-derived organoid lines was established. This panel recapitulates genetic and molecular characteristics previously described for HNSCC. Organoids retain their tumorigenic potential upon xenotransplantation. We observe differential responses to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
276
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 285 publications
(286 citation statements)
references
References 80 publications
8
276
0
2
Order By: Relevance
“…In the recent past, drug screens have also been reported for PDOs established from many other organs, including liver [40], ovarian [32] and stomach [33] tumours. In addition to drug screens, a recent study of head and neck tumours applied radiation screens in PDOs and compared the results with the clinical outcome [34]. Three patients relapsed after radiotherapy within one to six months, consistent with the finding that their organoid lines were classified as most resistant.…”
Section: In Vitro Culture Systemssupporting
confidence: 58%
See 1 more Smart Citation
“…In the recent past, drug screens have also been reported for PDOs established from many other organs, including liver [40], ovarian [32] and stomach [33] tumours. In addition to drug screens, a recent study of head and neck tumours applied radiation screens in PDOs and compared the results with the clinical outcome [34]. Three patients relapsed after radiotherapy within one to six months, consistent with the finding that their organoid lines were classified as most resistant.…”
Section: In Vitro Culture Systemssupporting
confidence: 58%
“…While these experiments are important to characterize in greater detail the interplay between tumour and immune cells, it needs to be shown to what degree they will add to the predictive value of organoids in clinical set-ups. First trial experiments using organoids for radiation and drug screens showed good correlation with the respective in vivo patient responses [33,34].…”
Section: Clinical Relevance and Implementationmentioning
confidence: 95%
“…For tubuloid experiments, the drug safety screening was performed using a protocol derived from Driehuis et al 64 . In short, BME was dissolved by incubation in 1 mg/mL dispase II for 30 min at 37…”
Section: Cell Viability Assaysmentioning
confidence: 99%
“…Because the organoids possess many functional and structural characteristics of the original tissue and retain their tumorigenic potential, this technology has now opened completely new perspectives in human research. Organoids generated from individual patients offer the future to study and identify molecular mechanisms in pathophysiology, in transformation and progression of tumor growth, screening and prediction of response and sensitivity to chemotherapeutic drugs, and ultimately the possibility of personalized therapy 6,7 .…”
mentioning
confidence: 99%